PENGARUH PROMOSI MELALUI MEDIA SOSIAL INSTAGRAM HARGA DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN DI AYAM GORENG SREENG NGADILUWIH - Shefyna Marta; Indah Yuni Astuti; Agung Pambudi Mahaputra (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
This research aims to test and explain the influence of promotions via social media Instagram, price and location on purchasing decisions at Ayam Goreng Sreeng Ngadiluwih partially and simultaneously. This research uses quantitative methods and the population studied is all consumers who purchased Ayam Goreng Sreeng Ngadiluwih within the 1 month research period. The number of samples taken was 100 respondents, and the sampling method was used accidental sampling. Data collected through questionnaires, while analysis techniques use validity tests, realism tests, classical assumption tests, multiple linear regression analysis, R determinant tests2, t test, and f test. The research results show that (1) the influence of promotion via Instagram social media partially has a significant effect on purchasing decisions with a sig. 0.000 < 0.05, (2) price partially has a significant effect on purchasing decisions with the t valuecount 5.076 and sig value. 0.000 < 0.05, (3) location partially has a significant effect on purchasing decisions with a sig value. 0.001 < 0.05, (4) promotion via social media Instagram, price and location simultaneously have a significant effect on purchasing decisions with a sig.F value of 0.000 < 0.05. Purchasing decisions at Ayam Goreng Sreeng Ngadiluwih are influenced by these three variables amounting to 63.9% while the remaining 36.1% is influenced by other factors outside this research.